Ambient PM2.5 exposure and risk of lung cancer incidence in North America and Europe. (28th February 2019) - Ghazipura, Marya; Garshick, Eric; Cromar, Kevin
Abstract: Regulatory analysis in the US has not previously identified lung cancer incidence as an adverse health outcome of fine particle air pollution (PM2.5 ). In an effort to provide the latest scientific knowledge in support of the pending scientific evaluation of PM2.5 by the US Environmental Protection Agency (EPA), a systematic review and meta-analysis was conducted to examine the relationship between long-term PM2.5 exposure and lung cancer incidence. We extracted data from four studies based on North American study populations and two studies based on European study populations in accordance with PRISMA guidelines. The results of the meta-analysis indicate a 25% increased risk of lung cancer incidence per 10 μ g m −3 increase in PM2.5 concentrations (RR = 1.25, 95% CI: 1.12–1.40), which is higher than previously published risks for lung cancer mortality. These effects were observed at concentrations relevant to current US standards. It is recommended that the EPA identifies lung cancer incidence, in addition to previous evidence for lung cancer mortality, as an adverse effect of long-term PM2.5 exposures.